PENGEMBANGAN PARIWISATA KABUPATEN SUKABUMI MELALUI TAGLINE GURILAPSS PESONA SUKABUMI - Mulya, Inda Sri; Hernawan, Denny; Fitriah, Maria (JURNAL KOMUNIKATIO, 2020)
Mountains, Wilderness, Sea, Beach, River and Cultural Art or often known as GURILAPSS are the characteristics of tourism in Sukabumi Regency, so when speaking GURILAPSS, Sukabumi is the destination. The formulation of the problem in this research is â€œHow is Sukabumi Tagline?â€. This study aims to determine the device to determine the tourism development of Sukabumi District throught the GURILAPSS Pesona Sukabumi Tagline.This study uses a centralized interview approach (Focused Interviews), with research. This research data collection technique uses two data sources, namely primary and secondary sources. Primary data obtained by interview and observation. Secondary data obtained by documentation. The key Informant in this study was the Head of tourism marketing and promotion in Sukabumi Regency. While supporting informant s consisted of one Head of Culture and one Head of Culture and six people of Sukabumi Regency.Technical analysis of data in this study using the model of Miles and Huberman. The results showed that the Tourism Development of Sukabumi Regency through the tagline GURILAPSS the result showed the Development of tourism in Sukabumi Regency through the tagline GURILAPSS the charm of Sukabumi uses three basic elements in its development, namely the emergence of motivation and desire for tourists to visit a tourism through the development of attractions and tourist attractions; there are supporting tourism facilities such as roads, accomodation, information centers and shopping centers through amenitas and tourist accommodation and transportation to take to tourist attraction. The conclusion in this study Sukabumi Regency tourism development through the tagline GURILAPSS enchanment Sukabumi has used aspect of the development of attractions and tourist attractions; tourist amenities and accomodations as well as tourist accesbility.Keywords:Â GURILAPSS Enchanting Sukabumi,Â  Tourism Development; Tagline.